Can Patients Select the Best Hospital for Carotid Revascularization?. Issue 6 (December 2015) - Chaturvedi, S.; Loftus, I.
Abstract : Background: Public reporting of cardiac surgery outcomes has been available for many years in the USA. Whether public information regarding carotid endarterectomy or stenting outcomes is available has not been studied previously. Methods: The Medicare Hospital Compare website was analyzed for carotid endarterectomy and stenting volume and complications data. Results: Within a large metropolitan area, endarterectomy volume data was provided in less than half of hospitals, with no information provided on morbidity or mortality. No information was available on carotid stenting. Conclusions: The quality of information available to patients in the USA contemplating a carotid revascularization procedure is suboptimal. Considering the volume of these procedures, greater transparency with regard to outcomes is desirable. Adoption of carotid procedure reporting practices as used in the UK should be considered.